Experiences of Violence and Treatment Of Aggression That Nurses Experience And See By Nurses In The Workplace: Literature Review - Iyus Yosep; Rohman Hikmat; Meideline Chintya; Nanda Amilia; Widya Nurwulan; Ai Mardhiyah (Science Midwifery, 2022)
Nurses are one of the health workers who are at risk of experiencing violence. In the last 10 years there has been a 110% spike in the rate of violent injuries to health care workers. Violence in the workplace can disrupt interpersonal relationships, damage people's self-esteem, affect physical and mental health and well-being, so that it will have an impact on the quality of care. This literature review uses a narrative review design which aims to find out the nurses' experiences of violence and aggressive treatment that have been experienced and seen. The article search method used the CINAHL database, PubMed database, and Science direct. The inclusion criteria for the articles used are articles with full text availability; in English and Indonesian, published in 2013-2022, are quantitative and qualitative research. Research respondents are nurses, and discuss the experiences of nurses against violence and aggressive treatment. In the article search, 12 articles were found that met the inclusion and exclusion criteria. Nurses' experiences regarding violence and aggression include physical, non-physical, emotional, psychological, and sexual violence. Nurses can be victims or perpetrators. One of the consequences of violence against nurses, one of which has an impact on a decrease in work. The physical violence experienced by nurses included being cornered, beaten, punched, bitten, stoned, grabbed, kicked, spat on, strangled, and threatened with sharp weapons. At the same time, non-physical violence against nurses more often took the form of verbal violence.